HUBUNGAN FREKUENSI KONSUMSI MAKANAN KARIOGENIK DAN PENGETAHUAN KESEHATAN GIGI DENGAN KARIES GIGI PADA ANAK SEKOLAH DASAR DI KOTA BENGKULU - Kamsiah, Kamsiah (Politeknik Kesehatan Kemenkes Bengkulu, 2012)
School age groups whose numbers are large enough and high enough teeth caries. One of the factors causing dental caries is a high consumption of cariogenic foods. According to the profile of the city of Bengkulu health, dental caries was ranked 15 of 21 patterns of disease outpatient clinic. Research Objectives. To Know the relationships and frequency of consumption of cariogenic dental health knowledge with dental caries in primary school children in the city of Bengkulu. Research Methods. Type of research is an observational study with cross-sectional research design. Subjects in this study were grade III-IV as many as 212 people Negeri 1, SD Negeri 4, SD Negeri 9, Bengkulu City Elementary School 74. The data analysis was performed with univariate and bivariate analysis, the use of statistics by using the Chi-square test and multivariate analysis with logistic regression statistical tests. Research. A total of 72.6% of respondents are cariogenic foods. Type of cariogenic foods are often consumed the sweets (22%), chocolate (20%) and ice cream (14%). There were 33.5% of respondents were regular dental checks. More than half of respondents (52.8%) were suffering from dental caries. Statistical test results obtained on disignifikan relationships between children with dental caries (p = 0.009). Children who are not regular dental memeriksaan 2.263 times likely to suffer from dental caries than children who regularly check their teeth. Obtained a significant relationship between the frequency of consumption of cariogenic foods with dental caries (p = 0.002). Children who frequently eat foods cariogenic 2.819 times likely to have dental caries than children who rarely eat cariogenic foods. Multivariate test results demonstrate knowledge of dental health is the most dominant factor affecting dental caries.